The Role of KH Munawwir on the Development of Qirā'āt Science in Indonesia - Syah, Faisal Ahmad Ferdian; Azzahra, Fatimah; Nurakhmet, Khairol (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
This research discusses the contribution of KH. Munawwir in developing and spreading the science of qirā'āt in Indonesia. As a scholar and Islamic education figure, he actively spread and strengthened the teachings of the Qur’an among the community. He was one of the scholars who first spread sanad qirā'āt in Indonesia. From his hands, great scholars were born who participated in spreading the knowledge of qirā'āt to various corners of the archipelago. This research aims to explore the history and influence of KH. Munawwir in the science of qirā'āt from various primary and secondary sources. The research results show that KH. Munawwir founded an Islamic boarding school and taught the science of qirā'āt to many students. His teaching and dissemination of qirā'āt knowledge had a positive impact on the development of Al-Qur’an reading in Indonesia. Islamic boarding school founded by KH. Munawwir became a leading center for qirā'āt learning, producing skilled and knowledgeable scholars of the Qur'an and qirā'āt. This great contribution has preserved Islamic culture and created a generation of competent Al-Quranists. It is hoped that this research will provide valuable insight into the importance of the role of KH. Munawwir in developing the science of qirā'āt in Indonesia.